2004
DOI: 10.1007/s10310-003-0063-x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of forest clear-cutting on soil temperature: a comparison between before and after cutting, and between clear-cut and control sites

Abstract: Soil temperature is one of the most important factors governing biological activity in the soil. This study was conducted to investigate how forest clear-cutting changes soil temperature. Soil temperatures at 0.5, 1.0, 2.0, and 3.0 m depths were measured in two neighboring forest watersheds (35∞12ЈN, 140∞06ЈE) in Chiba Prefecture, Japan, from 1994 to 2000. One watershed was clear-cut 5 years after the observations began. After clear-cutting, the annual mean soil temperature at 0.5, 1.0, 2.0, and 3.0 m depths r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
23
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 32 publications
6
23
0
3
Order By: Relevance
“…It may also be due to the increase in absorption of solar radiation by mineral soil due to removal of forest cover observed at the low altitude forest stand, a state of deforestation which has led to the warming of the soil which in turn causes increase of the soil temperatures. This is in consistent with the earlier report of Hashimoto and Suzuki [11]. Increase soil temperature at the two study sites during the summer months could be due to effect of the solar radiation and the heating up of the surrounding soil surface.…”
Section: Soil Temperaturesupporting
confidence: 82%
“…It may also be due to the increase in absorption of solar radiation by mineral soil due to removal of forest cover observed at the low altitude forest stand, a state of deforestation which has led to the warming of the soil which in turn causes increase of the soil temperatures. This is in consistent with the earlier report of Hashimoto and Suzuki [11]. Increase soil temperature at the two study sites during the summer months could be due to effect of the solar radiation and the heating up of the surrounding soil surface.…”
Section: Soil Temperaturesupporting
confidence: 82%
“…Significant reductions in daily thermal amplitudes under a rain forest were found by Ghuman & Lal (1987) in the humid belt of Nigeria when compared to those measured in an open area, and by Morecroft et al (1998) in woodland of pedunculate oak and sycamore in contrast to those observed under grass and bare soil. A similar effect was reported by Hashimoto & Susuki (2004), when annual thermal amplitudes before and after clearcutting of sugi and japanese cypress stands were compared.…”
Section: Thermal Wave Damping With Depthsupporting
confidence: 79%
“…Under canopy shading only, daily and annual variations of soil temperature are known to be reduced (Ghuman & Lal, 1987;Morecroft et al, 1998;Hashimoto & Susuki, 2004). Additional shelter provided by the litter layer may reduce further convective and radiative heat exchange between soil and atmosphere, but this effect may depend on both the degree of canopy cover and thickness of the layer (Johnson-Maynard et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Because of the complex topography in the Š umava Mountains, we modelled the influence of this factor on ST values. Temperature changes due to forest clear-cutting (Yoshino 1975;Hashimoto and Suzuki 2004) and/or by stress from bark beetle attacks (Weber 1971;Schmid 1976) has already been described by many authors. Nevertheless, this study is unique, because of the use of satellite data and topography normalisation.…”
Section: Introductionmentioning
confidence: 92%